THE IMPACT OF INTEGRATING AUTHENTIC MATERIALS ON LEARNER ENGAGEMENT AND LANGUAGE DEVELOPMENT - Faiz, Ahmad (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
The use of authentic materials in language learning has been recognized to have a positive impact on students' engagement and language development. Authentic materials provide relevant and meaningful learning contexts, which can increase students' motivation and participation and help them develop better communicative and linguistic skills. This study aims to evaluate the impact of integrating authentic materials on learners' engagement and their language development, focusing on improving speaking, listening, reading and writing skills. This study used a quasi-experimental method involving 90 students from three randomly selected classes. The research was conducted by measuring students' language skills before and after the application of authentic materials for six weeks. Measurements were made through initial and final tests, with data analyzed using descriptive statistics. The results showed a significant improvement in students' language skills after the application of authentic materials. The average improvement in speaking was 23.8%, listening was 28.2%, reading was 24.4%, and writing was 15.5%. The findings indicate that the use of authentic materials can effectively increase students' engagement and their language skills in a more relevant and meaningful context. This research shows that integrating authentic materials in language learning not only improves language skills but also students' motivation and engagement, which is essential for more effective and meaningful language learning.